Spindle speed modulation for chatter suppression in machining process - Amirul Hakim, Kamarazaman (2016)
In manufacturing industry, productivity rate and profit is crucial. Higher productivity rate means the product can be released fast, with good quality. Unfortunately to increase the productivity, manufacturer have to face a big challenge which is chatter. Chatter is a wavy marks on a product surface finish that occur when self—excited vibration develop during the process, results in bad surface finish and unpleasant sound. The objective of this study is to analyse and supress chatter by modulating the spindle speed in machining process and to analyse the cutting condition during normal and spindle speed variation method. Though many research has been done using accelerometer sensor to detect the vibrations, this project make a full use of acoustic sensor to achieve the same goals. This project also involve the development of a PID controller to give on-line feedback to the machine based on data fed by the sensor. Data from acoustic sensor is analysed in time and frequency domain. The result also comparing the surface roughness of all cutting condition. This project succeed in improving the surface roughness of the material up until 86.7% after spindle speed variation has been implemented and the objectives of this project has been achieve. On top of that, the overall project contribute to great improvement of productivity rate through higher Material Removal Rate (MIRR).